2022
DOI: 10.3390/catal12111367
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electronic Rearrangement and Synergistic Catalysis for Alkaline Water Splitting in Carbon-Encapsulated Ni (111)/Ni3C (113) Heterostructures

Abstract: The realization of efficient water electrolysis is still blocked by the requirement for a high and stable driving potential above thermodynamic requirements. An Ni-based electrocatalyst, is a promising alternative for noble-metal-free electrocatalysts but tuning its surface electronic structure and exposing more active sites are the critical challenges to improving its intrinsic catalytic activity. Here, we tackle the challenge by tuning surface electronic structures synergistically with interfacial chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…19,33,34 Since catalytic reactions properly occur at the lower coordination atomic sites, such as edges, corners, and kinky sites, the formation of surface vacancies would inevitably present such active sites. 35–42 For instance, Yu and co-workers reported that the strain- and defect-engineered Ni-MoS 2 monolayer exhibits a superior HER performance by promoting the rate-determining water dissociation step. 39…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,33,34 Since catalytic reactions properly occur at the lower coordination atomic sites, such as edges, corners, and kinky sites, the formation of surface vacancies would inevitably present such active sites. 35–42 For instance, Yu and co-workers reported that the strain- and defect-engineered Ni-MoS 2 monolayer exhibits a superior HER performance by promoting the rate-determining water dissociation step. 39…”
Section: Introductionmentioning
confidence: 99%
“…19,33,34 Since catalytic reactions properly occur at the lower coordination atomic sites, such as edges, corners, and kinky sites, the formation of surface vacancies would inevitably present such active sites. [35][36][37][38][39][40][41][42] For instance, Yu and co-workers reported that the strain-and defect-engineered Ni-MoS 2 monolayer exhibits a superior HER performance by promoting the rate-determining water dissociation step. 39 Inspired by the aforementioned concepts, we designed Rubased alloy nanoparticles (NPs) with a distorted surface structure in order to boost the HER kinetics in alkaline media.…”
Section: Introductionmentioning
confidence: 99%